Database Management / Objectives, System Functions, and Administration - Everest C. Gordon (Mcgraw Hill Book Company, 1986)
Preface, Overview of Database Management Systems, A Conceptual DBMS Model, Logical Data Structures, Database Management System Functions, Database Creation and Update, Data Independence and Data Conversion and Database Revision, Database Integrity: Access Control and Encryption, Database Administration, DBMS Selection and Acquisition, Trends to the Future in Database Management, Index.